Pengaruh Persepsi Peserta Didik Tentang Manfaat Tadarus Al-Qur’an dan Perhatian Orang Tua Terhadap Kedisiplinan Belajar - Arif Hantoro; Khoiruddin Nasution (Program Pascasarjana UNU Surakarta, 2022)
This study aims to determine the influence of students' perceptions of the benefits of the tadarus al-Qur'an and parents' attention to the learning discipline of class VIII students at SMP N 3 Polanharjo Klaten academic year 2020/2021. This research method uses a quantitative approach with a population of 43 students. Data analysis methods with classical assumption tests include linearity, normality, heteroskedasticity, multicollinearity, and multiple linear regression tests. The model accuracy tests are the F test, coefficient of determination (R2), and the hypothesis test with the T test. The study's results explained that the influence of students' perceptions of the benefits of qur'anic tadarus on the learning discipline of students at SMP N 3 Polanharjo Klaten Th 2020/2021 is positive and significant. This means that the higher the learner's perception of the benefits of the tadarus al- Qur'an, the higher the learning discipline. The influence of parents' attention on the learning discipline of students at SMP N 3 Polanharjo Klaten Th 2020/2021 is positive and significant. This means that the greater the attention of parents, the higher the learning discipline. The influence of students' perceptions of the benefits of the Qur'an tadarus and parents' attention to the learning discipline of students at SMP N 3 Polanharjo Klaten Th 2020/2021 together (simultaneously) is a significant effect